Designing a physical activity intervention for children with asthma: a qualitative study of the views of healthcare professionals, parents and children with asthma. Issue 3 (24th March 2017) - Jago, Russell; Searle, Aidan; Henderson, A John; Turner, Katrina M
Abstract : Objectives: Qualitative methods were used to examine: (1) the attitudes of health professionals to promoting physical activity for children with asthma; (2) reasons why children with asthma are less active and (3) how a physical activity programme for children with asthma could be designed. Design: Semistructured interviews were conducted with health professionals, children with asthma and their parents between October 2015 and March 2016. Interviews were transcribed verbatim and thematically analysed. Setting: Primary and secondary care in Bristol (UK). Participants: Interviews were held with 8 primary care practitioners (5 general practitioners, 2 nurse practitioners and 1 practice nurse), 9 parent–child dyads (2 fathers, 7 mothers, 6 sons, 3 daughters) of children aged 6–7 who had asthma and 4 secondary care professionals (2 respiratory consultants, 2 specialist nurses). Results: Health professionals reported that physical activity was beneficial for children with asthma and if managed appropriately, children with asthma could be as active as children without asthma. Current promotion of physical activity for children with asthma was limited and restricted by NHS staff time, access to inhalers at school and a lack of parental knowledge. Potentially important components of a new programme include parental education on the possibilities of activity for children with asthma and the difference between exercise-induced breathlessness and asthma symptoms. Other important elements include how to use inhalers as a preventive measure, coping with exacerbations and practical solutions (such as clearing sputum), managing transitions from warm to cold climates and general symptom control. Conclusions: There is a need to build on current asthma programmes to increase the support for children with asthma to be physically active. Future programmes could consider working more closely with schools, increasing parental knowledge and providing children with practical support to help be physically active.